2018
DOI: 10.1111/ajt.14873
|View full text |Cite
|
Sign up to set email alerts
|

Frailty phenotypes and mortality after lung transplantation: A prospective cohort study

Abstract: Frailty is associated with increased mortality among lung transplant candidates. We sought to determine the association between frailty, as measured by the Short Physical Performance Battery (SPPB), and mortality after lung transplantation. In a multicenter prospective cohort study of adults who underwent lung transplantation, preoperative frailty was assessed with the SPPB (n = 318) and, in a secondary analysis, the Fried Frailty Phenotype (FFP; n = 299). We tested the association between preoperative frailty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
105
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 109 publications
(110 citation statements)
references
References 65 publications
(167 reference statements)
3
105
2
Order By: Relevance
“…Each component is scored from 0 to 4, yielding an aggregate score ranging from 0 to 12. Lower SPPB scores reflect increased frailty, and a threshold ≤7 has been used in lung transplantation to define the frail state . Other studies have used different thresholds to define frailty by SPPB (eg, 6, 8, 9, 10), and prior work in COPD used a threshold of ≤9 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Each component is scored from 0 to 4, yielding an aggregate score ranging from 0 to 12. Lower SPPB scores reflect increased frailty, and a threshold ≤7 has been used in lung transplantation to define the frail state . Other studies have used different thresholds to define frailty by SPPB (eg, 6, 8, 9, 10), and prior work in COPD used a threshold of ≤9 .…”
Section: Methodsmentioning
confidence: 99%
“…Frailty, originally a geriatric construct, reflects accumulated deficits across physiologic systems that attenuate the body's physiologic reserve. We recently demonstrated that frailty is prevalent in lung transplant candidates and is independently associated with disability and delisting or death on the waiting list, as well as with death after lung transplantation . Recent studies in community‐dwelling and institutionalized older adults suggest that frailty may be reversible through exercise‐based intervention .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most screening tools for frailty are based on two concepts: "physical" or "phenotypic" frailty, versus "deficit accumulation" or "index" frailty. [22][23][24][25][26] Low muscle mass and function (known as sarcopenia) has also been used as an objective indicator of frailty and can be reliably measured by dual-energy X-ray absorptiometry (DEXA), or estimated by computed tomography (CT), magnetic resonance imaging, or bioimpedance. The testing takes under 10 minutes to administer, is easily implemented, and can be interpreted by nongeriatricians.…”
Section: Fr Ailt Y Me a Sure Smentioning
confidence: 99%
“…The subjects of this study had an average BMI of 21.1, but skeletal muscle mass was decreased to 84.1% and body fat mass was increased to 151.8%. 36 The most recent paper showed that frail LTx candidates derived significant benefit in functional capacity and health-related quality of life despite significant disability pretransplant. Therefore, in nonobese waitlisted ILD patients, reducing body fat mass by nutritional intervention cannot be recommended because it may instead decrease TTR and albumin and possibly promote sarcopenia, 30,31 which results in poor prognosis.…”
Section: Discussionmentioning
confidence: 99%